Determinants of Adoption of Artificial Insemination for Dairy Production: In Case of Zala Woreda, Gofa Zone, Southern Ethiopia - , Nuradis Adem; , Agidew Abebe (Archives of Current Research International, 2022)
Despite Ethiopia possessing the largest number of livestock in Africa, its benefit to the country and dairy holder farmers was small. Though the government introduced Artificial Insemination (AI) technology to improve this contribution, but the adoption of AI by dairy farmers was still low. The objective of the study was determinant factors affecting adoption of AI technology for dairy farmers in Gofa zone zala woreda. In this study both qualitative and quantitative data from Primary and secondary sources was collected. Survey questionnaires were used to collect raw data from AI adopters and non-adopters. AI adopters were selected by using purposive sampling because all sampled household heads were the only adopters in the study area whereas non-adopters were selected by using random sampling. The data was analyzed by using SPSS software. Descriptive statistics and binary regression model were used for analyzing data. A binary logit model was used to analyze the determinants of adoption of AI technology. Totally eleven variables were included in the model of which age of household head, training on AI, and frequency of DA contact were found significant at 1% (P<0.01) probability level. On the other hand household head’s educational level, access to AI information, and distance from AI center were significant at 5% (P<0.05) probability level. Finally an effort should be given by the woreda government and livestock and fishery development office in increasing rural adult education, expanding AI center, strengthening DA's regular contact with dairy farmers, strong and appropriate information should be disseminated and training on AI technology should be given, which widens the knowledge of farmers on the technology.